Primary Immunodeficiencies and Oncological Risk: The Experience of the Children's Hospital of Brescia - Maffeis, Marianna; Notarangelo, Lucia Dora; Schumacher, Richard Fabian; Soncini, Elena; Soresina, Annarosa; Lanfranchi, Arnalda; Porta, Fulvio (Frontiers in Pediatrics, 2019)
• Background and aims Primary immunodeficiencies (PID) are characterized by recurrent infections and increased risk of malignancies because of the reduced immunological surveillance against cancer cells and oncogenic viruses. • Methods We report the incidence of tumors among 690 patients with PID, diagnosed from 1990 until 2017 in Brescia. • Results Out of 690 patients , 25 patients (3.6%) developed 33 tumors. Of the 25 affected patients, 8 patients suffered from CVID, 5 from CID, 3 from AT, 2 from HSP2, 2 from XLA, 2 from WAS, 2 from HIES, 1 from SCID. The age at diagnosis ranged from 1 to 52 years, with a median age of 19.6 years. The time between the diagnosis of PID and onset of tumor was short, often <1 year between diagnosis and the appearance of cancer in the case of CID. Moreover, in two cases of CID, the diagnosis of cancer was made before the diagnosis of PID, so cancer was the onset clinical manifestation. Hematological malignancies were prevalent (22/33, 66.7%) with a minority of solid tumors (11/33, 33.33%). In particular Non Hodgkin lymphomas were the most frequent (16/33, 48.48%). In total 13 patients survived (52%) and tumor was the main cause of death (7 cases). Two patients underwent BMT once the disease was in remission. • Conclusions Therefore, the correct management of tumors that arise in patients with primitive immunodeficiency still represents a challenge in the pediatric field. For this reason now it is mandatory to collect in a unique international registry the cases of malignancies in PID that could lead to a better understanding of the etiopathogenesis and of the biological and clinical characteristics of these tumors, with the aim of defining adequate preventive measures and guaranteeing an early diagnosis which also creating a shared and specific therapeutic strategy, with the prospect of obtaining a better prognosis for these patients.